Growth, mortality and spawning stock biomass of the striped red mullet Mullus surmuletus, in the Egyptian Mediterranean waters - MEHANNA, S.F. (Mediterranean Marine Science, 2009)
Population parameters such as age, growth, mortality and maturity-at-age are crucial parameters for accurate stock assessment and management plans to ensure the sustainable development of fisheries. Also, they are essential for the calculation of spawning stock biomass (SSB) and equilibrium yield as well as biological reference points including Fmax, F0.1 and F30%SSB. Age and growth parameters were estimated for the striped red mullet, Mullus surmuletus, sampled from commercial landings of the trawl fishery in the Egyptian Mediterranean waters, using the otolith reading technique. M. surmuletus has a longevity of 5 years, but over 70% of fish were less than 2 years old. The growth parameter estimates were K= 0.47 yrs-1, L∞= 31.74 cm, and to= -0.3 yrs. Natural mortality (M) was 0.43 yrs-1, fishing mortality (F) was 0.73 yrs-1, survival rate (S) was 0.31 and exploitation ratio was 0.63 yr-1. Length-at-50% maturity was estimated at 15.1 cm TL, while the length at first capture was estimated at 11.6 cm TL. SSB analysis showed that effort reduction is strongly recommended such that F be reduced by 40% to rebuild spawner biomass to acceptable levels. Per-recruit analysis revealed that F should be reduced by about 27% to achieve the maximum Y/R. All approaches point to the need for drastic reduction in fishing pressure by about 30-40% in the Egyptian Mediterranean fisheries.